2012
DOI: 10.1177/0265407512456672
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of social support and disclosure on fertility-related stress

Abstract: L. (2013). Interactive effects of social support and disclosure on fertilityrelated stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 62 publications
3
34
0
1
Order By: Relevance
“…Disclosure carryover has been examined not only in mental illness but in areas such as infertility and HIV/AIDS (Chaudoir et al 2011, Corrigan & Rao 2013, Martins et al 2013, Rudolph et al 2012, Wade et al 2011). Thus, this dimension focuses on the negative consequences of disclosure.…”
Section: Stigma As a Multidimensional Concept: The Example Of Public mentioning
confidence: 99%
“…Disclosure carryover has been examined not only in mental illness but in areas such as infertility and HIV/AIDS (Chaudoir et al 2011, Corrigan & Rao 2013, Martins et al 2013, Rudolph et al 2012, Wade et al 2011). Thus, this dimension focuses on the negative consequences of disclosure.…”
Section: Stigma As a Multidimensional Concept: The Example Of Public mentioning
confidence: 99%
“…This inadequate perception that fertility treatments could reverse a natural decline can be due to the fact that while there is a high dissemination of successful stories among the general population 5 , couples seeking treatment often do not disclose their infertility for fear of not receiving social support 24 . Nevertheless, baseline knowledge regarding infertility risk factors was average in this sample.…”
Section: Findings and Interpretationmentioning
confidence: 99%
“…In particular, reasons why men do not disclose using ART to those outside of their immediate personal relationships tend to centre on shame (Lee and Chu, 2001) and fear of thoughtless comments (Throsby and Gill, 2004). This is problematic because research has shown that social support is associated with less stress (Martins et al, 2013) and less depression, and anxiety and greater positive adjustment to involuntary childlessness (Bute, 2013;Mahajan et al, 2009). …”
Section: Introductionmentioning
confidence: 99%